ACADEMIC MIGRATION OF UKRAINIAN STUDENTS AND ITS IMPACT ON THE INSTITUTIONAL ENVIRONMENT IN SLOVAKIA - BALOGOVÁ, Beáta; KOVALCHUK, Yuliia (Social work and education, 2024)
The article analyzes the issue of migration as a complex social phenomenon. International population migration in the conditions of growing globalization occupies an important place in the development of modern society and, accordingly, affects young people who, for various reasons, decided to study abroad (in Slovakia). The article reflects knowledge at the theoretical and empirical levels. One of the main tasks of modern higher education is the modernization and efficiency of the professional mobility of future specialists. Student migration is considered as educational migration.We point out that the Slovak Republic is one of the most economically successful countries in Central-Eastern Europe. Economic reforms and accession to the EU, combined with significant inflows of foreign direct investment, have led to sustained economic growth and job creation. Economic development and demographic changes have also created an additional need for skilled labor. At the same time, greater integration into the EU, open borders and a common educational space led to the migration of Slovak students to the neighboring Czech Republic and other EU countries. As a result, Slovakia gradually began to ease migration restrictions and allowed an increasing number of third-country nationals to enter the territory of the Slovak Republic. The integration policy of Slovakia is consistent with the migration policy, and among its priorities is the effective integration of foreigners in the labor market.The purpose of the article is to analyze Ukrainian student migration in Slovakia, focusing on the analysis of personal and social benefits. We analyze the issue of academic mobility as an integral component of the European educational space, which also undoubtedly has a positive effect on the national education system and the national economy. We highlight the issue of effective ethnic-national policy formation, development of theory and practice of social work with ethnic groups, find out directions and forms of social service work with migrants.In the empirical part, we present a quantitative study at all stages of the research process. The content of the study is to find out the reasons that motivate future Ukrainian students to migrate to Slovakia, as well as to find out how the initial decision about migration and arrival to Slovakia takes place. Part of the quantitative research is the analysis of the personal and social benefits of the migration of Ukrainian students to Slovakia.